Changes in the anti-lipolytic action and binding to plasma membranes of N6-L-phenylisopropyladenosine in adipocytes from starved and hypothyroid rats. - Chohan, P (1984)
The anti-lipolytic effect of the adenosine analogue N6-L-phenylisopropyladenosine was studied with rat adipocytes incubated with a high concentration of adenosine deaminase (0.5 unit/ml, approx. 2.5 micrograms/ml) and concentrations of noradrenaline that were equieffective in different physiological states. These studies were performed to compare the fed and starved (24h) states and to compare a hypothyroid state (induced by feeding propylthiouracil + a low-iodine diet) with the euthyroid state. Starvation increased sensitivity of the cells to the lipolytic action of noradrenaline, while decreasing sensitivity to the antilipolytic action of phenylisopropyladenosine. Hypothyroidism resulted in decreased sensitivity to noradrenaline and increased sensitivity to phenylisopropyladenosine. Studies of the binding of [3H]phenylisopropyladenosine to adipocyte plasma membranes indicated heterogeneity of binding sites or negative co-operativity in the binding. Starvation did not change [3H]phenylisopropyladenosine binding to membranes, whereas hypothyroidism caused an unexpected decrease in both the number and affinity of the binding sites. These observations are discussed in terms of the dual regulation of adipose-tissue lipolysis by lipolytic and anti-lipolytic agents.